Prenatal Diagnosis for Primary Immunodeficiency Disorders—An Overview of the Indian Scenario - Yadav, Reetika Malik; Gupta, Maya; Dalvi, Aparna; Bargir, Umair Ahmed; Hule, Gouri; Shabrish, Snehal; Aluri, Jahnavi; Kulkarni, Manasi; Kambli, Priyanka; Uppuluri, Ramya; Seshadri, Suresh; Jagadeesh, Sujatha; et al. (Frontiers in Immunology, 2020)
Prenatal Diagnosis (PND) forms an important part of primary preventive management for families having a child affected with primary immunodeficiency. Although individually sparse, collectively this group of genetic disorders represents a significant burden of disease. This paper discusses the prenatal services available for affected families at various centers across the country and the challenges and ethical considerations associated with genetic counseling. Mutation detection in the index case and analysis of chorionic villous sampling or amniocentesis remain the preferred procedures for PND and phenotypic analysis of cordocentesis sample is reserved for families with well characterized index case seeking PND in the latter part of the second trimester of pregnancy. A total of 112 families were provided PND services in the last decade and the presence of an affected fetus was confirmed in 32 families. Post-test genetic counseling enabled the affected families to make an informed decision about the current pregnancy.